Child survival in England: Strengthening governance for health. Issue 11 (November 2017) - Wolfe, Ingrid; Mandeville, Kate; Harrison, Katherine; Lingam, Raghu
Highlights: Child health and survival in England is worse than in comparable countries. This is the first study of child health policy governance and conditions. We identified strengths and weaknesses in child health governance and non-governance conditions. Recommendations for child health governance, policy, and action are made. Lessons derived from the English policy context are applicable elsewhere in Europe. Abstract: The United Kingdom, like all European countries, is struggling to strengthen health systems and improve conditions for child health and survival. Child mortality in the UK has failed to improve in line with other countries. Securing optimal conditions for child health requires a healthy society, strong health system, and effective health care. We examine inter-sectoral and intra-sectoral policy and governance for child health and survival in England. Literature reviews and universally applicable clinical scenarios were used to examine child health problems and English policy and governance responses for improving child health through integrating care and strengthening health systems, over the past 15 years. We applied the TAPIC framework for analysing policy governance: transparency, accountability, participation, integrity, and capacity. We identified strengths and weaknesses in child health governance in all the five domains. However there remain policy failures that are not fully explained by the TAPIC framework. Other problems with successfully translating policy to improved health that we identified include policy flux; policies insufficiently supported by delivery mechanisms, measurable targets, and sufficient budgets; and policies with unintended or contradictory aspects. We make recommendations for inter-sectoral and intra-sectoral child health governance, policy, and action to improve child health in England with relevant lessons for other countries.